2017
DOI: 10.1177/1534484317725967
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Work Engagement and Organizational Commitment: Proposing Research Agendas Through a Review of Empirical Literature

Abstract: Work engagement and organizational commitment are among the most studied topics in a range of fields, including human resource development (HRD) and organization development (OD). The value of such work is evident in the direct influence of work engagement and organizational commitment on employee well-being and organizational performance. However, scholars have divergent perspectives on the relationship between these two concepts. While some studies have examined work engagement as a precursor to organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 56 publications
5
60
0
5
Order By: Relevance
“…These results are consistent with Allen’s (2013) finding that the indirect satisfaction of employees’ needs through volunteering could serve as a basis for a positive correlation between these two constructs. However, some authors (e.g., Caudron, 1994; Booth et al, 2009; Breitsohl and Ehrig, 2016; Rodell et al, 2016, 2017) have reported a positive effect of corporate volunteering on other organizational behaviors (productivity, job satisfaction, sense of belonging, performance), which are positively correlated with work engagement (Harter et al, 2013; Karanika-Murray et al, 2014; Kim et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with Allen’s (2013) finding that the indirect satisfaction of employees’ needs through volunteering could serve as a basis for a positive correlation between these two constructs. However, some authors (e.g., Caudron, 1994; Booth et al, 2009; Breitsohl and Ehrig, 2016; Rodell et al, 2016, 2017) have reported a positive effect of corporate volunteering on other organizational behaviors (productivity, job satisfaction, sense of belonging, performance), which are positively correlated with work engagement (Harter et al, 2013; Karanika-Murray et al, 2014; Kim et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Work engagement is in fact a specific construct, different from constructs such as loyalty to the organization or work inclusion, with which it is occasionally conflated in practice (Bakker and Leiter, 2010). It is positively associated with constructs such as work performance, productivity (Harter et al, 2013), organizational commitment (Kim et al, 2017), organizational identification, job satisfaction (Karanika-Murray et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigor refers to energy and resilience in work; dedication means one’s deep involvement in work and in experiencing associated feelings of significance, enthusiasm, and challenge; and absorption refers to the state of being totally absorbed and actively engaged in work. Although work engagement is a multi-dimensional concept, this study examines it as an integral construct, consistent with most of the literature (e.g., [65,66]).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 92%
“…Work engagement has become a popular topic for organizations and researchers, especially as it usually brings desirable outcomes for different types of organizations and individuals [65]. Many studies have explored the antecedents and outcome variables of work engagement (e.g., [29,30]).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%